The Gothic Uncanny: Selected Mind-Images in Literature and Film - Corrêa, Graça P. (2019)
The concept of the uncanny has been a focus of critical, literary, and philosophical reflection since the nineteenth century. Nonetheless, especially in continental Europe, two essays on the subject—both written in German, from the early twentieth century—particularly stand out: the first by Ernst Jentsch in 1906 (“On the Psychology of the Uncanny”); the second by Sigmund Freud in 1919 (“The Uncanny”). Although distinct, these two reflections on the uncanny are admittedly inspired by a tale of Gothic fiction of the early nineteenth century written by E.T.A. Hoffmann and entitled “The Sandman” (1817). In this article, I approach the Gothic uncanny of family relations as evoked in tales by E.T.A. Hoffmann and Edgar Allan Poe, and in films by Alfred Hitchcock, David Lynch and Stanley Kubrick. Although Gothic fiction’s tendency to render everyday objects and events disturbingly terrifying and strange has been predominantly investigated through Freudian psychoanalytic lenses, I will draw on schizoanalysis and the Deleuzian time-image to supplement and challenge existing psychoanalytic assessments of the uncanny.